The Flipped Classroom - Changing the Traditions in Medical Education - Tayyaba Ahmed (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Medical education around the world is rapidly evolving which warrants a need for new and improved teaching methods. Many new models are being tested around the world to check for their efficacy in comparison to traditional classroom teaching. One of the most researched teaching models in the recent past is the 'flipped classroom model'. It has been labelled as the new paradigm for medical education.